CD146 interaction with integrin β1 activates LATS1-YAP signaling and induces radiation-resistance in breast cancer cells. (10th October 2022) - Liang, Yuanke; Zhou, Xiaoling; Xie, Qin; Sun, Hexing; Huang, Kaiyuan; Chen, Huan; Wang, Wende; Zhou, Benqing; Wei, Xiaolong; Zeng, De; Lin, Haoyu
Abstract: Radiotherapy is an indispensable modality in comprehensive treatment of breast cancer. However, inherent or acquired radiation resistance of tumors compromises the efficacy of radiotherapy. Herein, we found that CD146, a unique epithelial-to-mesenchymal transition (EMT) inducer particularly highly expressed in triple-negative breast cancer (TNBC), is dramatically induced by ionizing irradiation. Further study demonstrates that CD146 promotes tumor cell radioresistance in vitro and in vivo . Specifically, we report the underlying mechanism that CD146 activates YAP protein, and drives its relocation from plasma to nucleus by regulating LATS1, and promoting abnormal DNA damage repair, as well as inducing EMT and stemness. Moreover, CD146 can form a novel co-receptor complex with integrin β1 and induces radiation-resistance in breast cancer. Dual inhibition of CD146 and integrin β1 activity had a stronger inhibitory effect on breast cancer tumor growth and synergistically increased their sensitivity to radiotherapy. This study identifies a unique function of CD146 implicates with integrin β1 and YAP signaling, contributing to radiation resistance. Targeted therapy against CD146 or inhibition of integrin β1 is a potential strategy to overcome radiotherapeutic resistance of breast cancer. Highlights: CD146 promotes DNA damage response and radioresistance in breast cancer cells. CD146 is a critical cell membrane mediator of LATS1-YAP signaling. CD146 interaction with integrin β1 mediates radioresistance in breast cancer cells.